Skip to Main Content
It looks like you're using Internet Explorer 11 or older. This website works best with modern browsers such as the latest versions of Chrome, Firefox, Safari, and Edge. If you continue with this browser, you may see unexpected results.


Other Trigonometric Integrals

Often we have to apply trigonometric identities before integrating. This is required when integrating the form where and n are integers, \(\int \sin^m x\cos^n x\,dx\). For this form of integrals, there are three cases to consider.

Case 1. m is odd.

  1. Write \(\sin^m x\) as \(\sin^{m-1} x\sin x\)
  2. Use \(\cos^2 x+\sin^2 x=1\) to write the even power of sines in terms of cosines
  3. Use the substitution \(u=\cos x\)

Case 2. is odd.

  1. Write \(\cos^n x\) as \(\cos^{n-1} x\cos x\)
  2. Use \(\cos^2 x+\sin^2 x=1\) to write the even power of cosines in terms of sines
  3. Use the substitution \(u=\sin x\)

Case 3. Both m and are even

Use \(2\cos^2 x=1+\cos 2x\) and \(2\sin^2 x=1-\cos 2x\) to halve the even powers.

Example 1: Integrate \(\int \sin^3 x\cos^6 x\,dx\)

Solution: We can use the steps outlined in Case 1 since \(m=3\).

\[\int \sin^3 x\cos^6 x\,dx=\int \sin^2 x\sin x\cos^6 x\,dx\]

Now we substitute \(\sin^2 x=1-\cos^2 x\)

\[\int \sin^2 x\sin x\cos^6 x\,dx=\int \left(1-\cos^2 x\right)\sin x\cos^6 x\,dx=\int \sin x\cos^6 x\,dx-\int \sin x\cos^8 x\,dx\]

Now let \(u=\cos x\), then \(du=-\sin x\,dx\)

\begin{align} \int \sin x\cos^6 x\,dx-\int \sin x\cos^8 x\,dx &= \int u^6\,du-\int u^8\,du \\ &= \frac{u^7}{7} -\frac{u^9}{9}+C \\ &= \frac{\cos^7 x}{7} -\frac{\cos^9 x}{9}+C \end{align}

Example 2: Integrate \(\int \cos^2 2x\,dx\)

Solution: For this integral, we will follow the steps for Case 3 and use our double angle identities

\begin{align} \int \cos^2 2x\,dx&=\int \frac{1+\cos 4x}{2}dx\\&=\int \frac{1}{2} + \int \frac{\cos 4x}{2} \\ &=\frac{x}{2}+\frac{\sin 4x}{8}+C\end{align}

For the integrals of the form \[\int \tan^m x\sec^nx\,dx\] or \[\int \cot^m x\csc^nx\,dx\]

Case 1. and are both odd

  1. Set aside a factor \(\sec x\tan x\) or \(\csc x\cot x\)
  2. Use equations \(1+\tan^2x=\sec^2x\) to write the even power of tangents in terms of secants, or \(1+\cot^2x=\csc^2x\) to write the even power of cotangents in terms of cosecants
  3. Use the substitution \(u=\sec x\) or \(u=\csc x\)

Case 2. n is even

  1. If possible, set aside a factor \(\sec^2 x\) or \(\csc^2 x\). If not possible, use \(1+\tan^2x=\sec^2x\) to change a factor \(tan^2x\) into a term with  \(\sec^2 x\), or \(1+\cot^2x=\csc^2x\) to change a factor \(cot^2x\) into a term with \(csc^2x\). Repeat if necessary.
  2. Use \(1+\tan^2x=\sec^2x\) to write the even power of secants in terms of tangents, or \(1+\cot^2x=\csc^2x\) to write the even power of cosecants in terms of cotangents
  3. Use the substitution \(u=\tan x\) or \(u=\cot x\)

Case 3. is even, n is odd

  1. Use \(1+\tan^2x=\sec^2x\) to write the even power of tangents in terms of secants, or \(1+\cot^2x=\csc^2x\) to write the even power of cotangents in terms of cosecants
  2. Integrate the odd power of secants or cosecants by parts

Example 3: Integrate \(\int_{0}^{\pi/4} \tan x\sec^4 x\,dx\)

Solution: Let's set aside a \(\sec^2 x\) and use the identity \(\sec^2 x = 1+\tan^2 x\)

\begin{align} \int_{0}^{\pi/4} \tan x\sec^4 x\,dx&=\int_{0}^{\pi/4} \tan x\sec^2 x\left(1+\tan^2\right)dx \\ &= \int_{0}^{\pi/4} \tan x\sec^2 x +\int_{0}^{\pi/4} \tan^3 x\sec^2 x \end{align}

Let \(u=\tan x\), then \(du=\sec^2 x\,dx\)

\begin{align} \int_{0}^{\pi/4} \tan x\sec^2 x +\int_{0}^{\pi/4} \tan^3 x\sec^2 x &= \int_{x=0}^{x=\pi/4} u\,du +\int_{0}^{\pi/4} u^3 du \\ &= \left(\frac{u^2}{2} + \frac{u^4}{4}\right)_{x=0}^{x=\pi/4} \\ &=\left(\frac{\tan^2 x}{2} + \frac{\tan^4 x}{4}\right)_{0}^{\pi/4} \\&=\frac{3}{4}\end{align}

Alternative Solution: We can set aside \(\sec x\tan x\) instead and solve this another way.

\[\int_{0}^{\pi/4} \tan x\sec^4 x\,dx=\int_{0}^{\pi/4} \left(\tan x\sec x\right)\sec^3 x\,dx\]

Let \(u=\sec x\), then \(du=\sec x\tan x\,dx\). When \(x=0\), \(u=1\) and when \(x=\pi/4\), \(u=\sqrt{2}\)

\begin{align} \int_{0}^{\pi/4} \left(\tan x\sec x\right)\sec^3 x\,dx &= \int_{1}^{\sqrt{2}} u^3 du \\ &= \left(\frac{u^4}{4}\right)_{1}^{\sqrt{2}} \\&= \frac{3}{4} \end{align}

Example 4: Integrate \(\int \frac{1-\cot x}{\sin^4 x}dx\)

Solution: In some cases, you will have to use trigonometric identities and simplify before integrating

\begin{align} \int \frac{1-\cot x}{\sin^4 x}dx&=\int \frac{1}{\sin^4 x}dx- \int \frac{\cot x}{\sin^4 x}dx \\ &= \int \sec^4 x\,dx - \int \frac{\frac{\cos x}{\sin x}}{\sin^4 x}dx \\ &=  \int \left(1+\tan^2 x\right)\sec^2 x\,dx -  \int \frac{\cos x}{\sin^5 x}dx\\ &= \int\sec^2x\,dx+\int \tan^2x\sec^2 x\,dx -  \int \frac{\cos x}{\sin^5 x}dx \end{align}

For the second integral, let \(u=\tan x\), then \(du=\sec^2 x\,dx\). For the third integral, let \(v=\sin x\), then \(dv=\cos x\,dx\). 

\begin{align} \int\sec^2x\,dx+\int \tan^2x\sec^2 x\,dx -  \int \frac{\cos x}{\sin^5 x}dx &= \int\sec^2x\,dx+\int u^2\,du-\int v^{-5}\,dv \\&=\tan x+\frac{u^3}{3}-\frac{v^{-4}}{-4} +C\\&=\tan x+\frac{\tan^3x}{3}+\frac{\sin^{-4}x}{4}+C  \end{align}

Example 5: Integrate \(\int\frac{\sec^2t\tan t}{4+\sec^2t}dt\)

Solution: Sometimes you have to apply multiple techniques. In this case, the denominator is of the power -1. This suggests a logarithmic integral. So we let \(u=4+\sec^2t\), then \(du=2\sec t\left(\sec t\tan t\right)\,dt\)

\begin{align} \int\frac{\sec^2t\tan t}{4+\sec^2t}dt &= \frac{1}{2}\int\frac{du}{u} \\&= \frac{1}{2} \ln|u|+C \\&= \frac{1}{2} \ln|4+\sec^2t|+C\end{align}

Creative Commons License
Designed by Matthew Cheung. This work is licensed under a Creative Commons Attribution 4.0 International License.

chat loading...